Carbonic Anhydrases Function in Anther Cell Differentiation Downstream of the Receptor-Like Kinase EMS1. Issue 6 (18th May 2017) - Huang, Jian; Li, Zhiyong; Biener, Gabriel; Xiong, Erhui; Malik, Shikha; Eaton, Nathan; Zhao, Catherine Z.; Raicu, Valerica; Kong, Hongzhi; Zhao, Dazhong
Abstract : β-Carbonic anhydrases are posttranslationally modified by EMS1 and act as direct downstream effectors of this receptor-like kinase, highlighting their crucial role in cell differentiation. Abstract: Plants extensively employ leucine-rich repeat receptor-like kinases (LRR-RLKs), the largest family of RLKs, to control a wide range of growth and developmental processes as well as defense responses. To date, only a few direct downstream effectors for LRR-RLKs have been identified. We previously showed that the LRR-RLK EMS1 (EXCESS MICROSPOROCYTES1) and its ligand TPD1 (TAPETUM DETERMINANT1) are required for the differentiation of somatic tapetal cells and reproductive microsporocytes during early anther development in Arabidopsis thaliana . Here, we report the identification of β-carbonic anhydrases (βCAs) as the direct downstream targets of EMS1. EMS1 biochemically interacts with βCA proteins. Loss of function of βCA genes caused defective tapetal cell differentiation, while overexpression of βCA1 led to the formation of extra tapetal cells. EMS1 phosphorylates βCA1 at four sites, resulting in increased βCA1 activity. Furthermore, phosphorylation-blocking mutations impaired the function of βCA1 in tapetal cell differentiation; however, a phosphorylation mimic mutation promoted the formation of tapetal cells. βCAs are also involved in pH regulation in tapetal cells. Our findings highlight the role of βCA in controlling cell differentiation and provide insights into the posttranslational modification of carbonic anhydrases via receptor-like kinase-mediated phosphorylation.